2013
DOI: 10.4103/0970-0358.113709
|View full text |Cite
|
Sign up to set email alerts
|

Anthropomorphic and perforator analysis of anterolateral thigh flap in Indian population

Abstract: Background:Anterolateral thigh (ALT) flap is one of the most common flaps in the reconstruction armamentarium of plastic surgeons, but there is no published data about the flap characteristics in the Indian population. The aim of this study is to analyse the anthropomorphic characteristics of the ALT flap and the perforator details in Indian population.Materials and Methods:ALT flap details were studied in 65 patients of Indian origin comprising 45 males and 20 females. The study period is from August 2011 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For the racial differences, in one research, the English people had thicker thigh skin than Chinese . However, in other papers, similar thicknesses were reported (Table ) …”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…For the racial differences, in one research, the English people had thicker thigh skin than Chinese . However, in other papers, similar thicknesses were reported (Table ) …”
Section: Discussionmentioning
confidence: 75%
“…The thickness including the skin and hypodermis of the thigh area varied according to the race, measuring methods, and sex. Generally, females had thicker thigh flap than male . For the racial differences, in one research, the English people had thicker thigh skin than Chinese .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In Taiwan, Shieh et al [ 16 ] reported 83.8% MC perforators and 16.2% SC perforators, and Wei et al [ 5 ] reported that MC perforators account for 87.1% of perforators. In India, Seetharaman et al [ 18 ] have found 61.8% of MC perforators in India. In a cadaveric study, Choi et al [ 24 ] reported that MC perforators accounted for 82.5% of 160 perforators, while SC perforators accounted for 17.5% ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%